2010
DOI: 10.1111/j.1468-1331.2009.02946.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based epidemiologic study of Wilson’s disease in Taiwan

Abstract: This is the first population-based epidemiologic study of Wilson's disease in Taiwan. Because of the effective and affordable treatment, the prevalence of Wilson's disease in Taiwan is expected to increase continuously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
3
22
0
1
Order By: Relevance
“…Other limitations of the NHIRD have been discussed in our previous NHIRD studies [10][11][12][13][14] . However, for the present study, the limitations have only a trivial effect, because ICD-9 code 321.0 is very specific and the discharge diagnosis of cryptococcal meningitis is usually straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of the NHIRD have been discussed in our previous NHIRD studies [10][11][12][13][14] . However, for the present study, the limitations have only a trivial effect, because ICD-9 code 321.0 is very specific and the discharge diagnosis of cryptococcal meningitis is usually straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis is a common and destructive chronic systemic inflammatory disease with the average age-adjusted annual incidence rate 15.8 per 100 000 in Taiwan. 1,2 A systematic review and meta-analysis has shown that there is an increased incidence of cardiovascular events in patients with RA, such as acute myocardial infarction, stroke, and cardiac death. 3 Most studies investigating mortality in patients with RA compared to those without RA have found increased mortality rates largely due to cardiovascular diseases (CVD), specifically coronary artery diseases (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously established the population-based epidemiological data of motor neuron diseases [9] , Creutzfeldt-Jakob disease, multiple sclerosis [10] and Wilson's disease [11] from the National Health Insurance Research Database (NHIRD). At least 215 studies utilizing the same database have been published.…”
mentioning
confidence: 99%